Peran Program Bunda Mandiri Sejahtera Dalam Meningkatkan Kemandirian Ekonomi Keluarga Yatim (Studi Kasus LAZ Yatim Mandiri Purwokerto) - Aulia Rahman; Nabila Putri Khairunnisa; Syafril Firman Syah; Mahardhika Cipta Raharja (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2026)
Poverty remains a problem faced by many orphaned families due to the loss of the household’s primary source of income. This situation underscores the need for economic empowerment programs that go beyond providing consumptive aid and are capable of fostering sustainable economic self-reliance. This study aims to analyze the role of the Bunda Mandiri Sejahtera (BISA) Program, organized by LAZ Yatim Mandiri Purwokerto, in enhancing the economic self-reliance of orphaned families and to identify the factors supporting the program’s success. The study employs a qualitative method using a case study approach. Data were collected through semi-structured interviews, documentation, and literature review, and were analyzed using the Miles and Huberman model, which includes data reduction, data presentation, and drawing conclusions. The results indicate that the BISA Program plays a significant role in enhancing the economic self-reliance of orphaned families through the provision of business capital, entrepreneurship training, business mentoring, and spiritual guidance. This program has had a positive impact in the form of increased income, the growth of productive businesses, improved business management skills, and the development of a sense of independence and productivity among beneficiaries. In addition, ongoing mentoring has been a key factor in the program’s success, as it helps participants overcome various business challenges and strengthens their motivation to engage in entrepreneurship. The findings of this study indicate that productive zakat can function not only as an instrument for distributing aid but also as a means of economic empowerment capable of improving the long-term well-being and self-reliance of orphaned families. Therefore, efforts to strengthen mentoring, training, and capacity building for beneficiaries must continue to enhance the effectiveness of productive zakat-based empowerment programs.